Black Middle-class Masculinities in Postapartheid South Africa: Consumerism, Fashion and the Portrayal of Masculine Identities in Destiny Man Magazine. (2nd January 2019) - Leopeng, Bandile; Langa, Malose
Abstract: This article examines the state of middle-class black South African masculinity in the postapartheid era as presented in Destiny Man, a popular lifestyle magazine targeted at accomplished, stylish, and affluent black men in South Africa. The magazine offers a blend of compelling and relevant business and lifestyle content, including articles on fashion, grooming, sport, technology, and motoring. This article's focus on consumerism, fashion, and masculinity as represented and featured in the magazine offers a vital contribution to fashion studies in general and to the African diaspora's dress sense in particular, as well as to the contemporary intersections of wealth associated with masculine identification Articles published in the 2014 issues of the magazine were selected for an in-depth multimodal discourse analysis of how factors such as fashion, access to economic resources, status, and wealth play a significant role in masculine black identity formation. Visuals were also analysed to understand the representation of black middle-class men in the magazine. The findings indicate that Destiny Man 's characterization of middle-class black South African masculinity is based on the acquisition of material goods, on perceptions of power and on the ability to transition into formerly white-only spheres.